The compartmentalised nature of neuronal mitophagy: molecular insights and implications. - Fivos Borbolis; Palikaras, Konstantinos (Expert Rev Mol Med, 2022)
The maintenance of a healthy mitochondrial network and the ability to adjust organelle population in response to internal or external stimuli are essential for the function and the survival of eukaryotic cells. Over the last two decades several studies have demonstrated the paramount importance of mitophagy, a selective form of autophagy that removes damaged and/or superfluous organelles, in organismal physiology. Post-mitotic neuronal cells are particularly vulnerable to mitochondrial damage, and mitophagy impairment has emerged as a causative factor in multiple neurodegenerative pathologies, including Alzheimer's disease and Parkinson's disease among others. Although mitochondrial turnover is a multifaceted process, neurons have to tackle additional complications, arising from their pronounced bioenergetic demands and their unique architecture and cellular polarisation that render the degradation of distal organelles challenging. Mounting evidence indicates that despite the functional conservation of mitophagy pathways, the unique features of neuronal physiology have led to the adaptation of compartmentalised solutions, which serve to ensure seamless mitochondrial removal in every part of the cell. In this review, we summarise the current knowledge concerning the molecular mechanisms that mediate mitophagy compartmentalisation and discuss their implications in various human pathologies.
Keywords: Autophagy; Humans; Mitochondria; Mitochondrial Turnover; mitophagy; Neurons